The Role of the Aryl Hydrocarbon Receptor: Exploring Therapeutic Potential of Tapinarof in Neuroinflammation Using Activated Microglia. - El-Baz El-Motayam, Rana Mahmoud Ahmed (AUC Knowledge Fountain, 2026)
Neuroinflammation is a key contributor to neurodegenerative disease progression, driven by chronic microglial activation. The aryl hydrocarbon receptor (AhR) has emerged as an important regulator of inflammatory and antioxidant responses in microglia, however, AhR activation can produce divergent outcomes depending on the activating ligand. This study aimed to compare the effects of the selective AhR agonist tapinarof with those of the classical environmental ligand benzo[a]pyrene (B[a]P) on inflammatory and antioxidant signaling in activated microglial cells. Using LPS-stimulated SIM-A9 microglia, cell viability, nitric oxide production, time- and concentration-dependent gene expression, cytokine secretion, and pathway-specific knockdown of AhR and Nrf2 were assessed. Tapinarof significantly reduced LPS-induced nitrite production and suppressed the expression of key pro-inflammatory genes, while promoting controlled induction of antioxidant markers associated with Nrf2 signaling. In contrast, B[a]P failed to attenuate nitric oxide production, showed weaker inhibition of inflammatory gene expression, and induced cytotoxicity at higher concentrations despite activating canonical AhR target genes. Time-course analysis identified a window of 4 hours in which ligand-specific regulatory effects were most evident. Gene silencing experiments confirmed that tapinarof’s anti-inflammatory effects require functional crosstalk with the Nrf2 pathway. In conclusion, the findings demonstrate that selective AhR modulation by tapinarof promotes anti-inflammatory and antioxidant responses in activated microglia, whereas xenobiotic AhR activation by B[a]P has shown limited inflammatory control. This study highlights the importance of ligand-specific AhR signaling and supports the AhR–Nrf2 axis as a potential target for modulating microglial-driven neuroinflammation.